Pelvic magnetic resonance imaging parameters predict urinary incontinence after robot‐assisted radical prostatectomy. Issue 3 (12th December 2018) - Sadahira, Takuya; Mitsui, Yosuke; Araki, Motoo; Maruyama, Yuki; Wada, Koichiro; Edamura, Kohei; Kobayashi, Yasuyuki; Watanabe, Masami; Watanabe, Toyohiko; Nasu, Yasutomo
Abstract : Objective: Urinary incontinence (UI) is a major prostate cancer (PCa) treatment‐related morbidity. It has been reported that post‐prostatectomy UI is related to the width of the pelvic floor muscles (PFM) and the length of the urethra. However, the details of these anatomical parameters are unknown. The aim of this study was to investigate whether preoperative pelvic parameters or anatomical parameters of the urethra, as measured by magnetic resonance imaging (MRI), are correlated with UI. Methods: Between 2010 and 2017, 571 patients with localized PCa underwent robot‐assisted radical prostatectomy (RARP) at Okayama University Hospital. Patients treated by a single experienced surgeon were included in the study. Preoperative prostate volume, obturator internal muscle, anal sphincter muscle, levator ani muscle (LAM), urethra wall thickness (UWT), and membranous urethral length (MUL) were measured by MRI. Patients were divided into two groups depending on leakage status 1 year after RARP using Expanded Prostate Index Composite Item 1. Results: Seventy patients were included in this retrospective study. Based on leakage status, 37 and 33 patients were allocated to the no‐leakage and leakage groups, respectively. There were significant differences between the two groups in age ( P = 0.03), MUL ( P < 0.001), UWT ( P = 0.03), and LAM ( P = 0.001). Multivariate logistic regression analyses revealed that MUL and LAM predicted UI 1 year after RARP. Conclusions: Pelvic parameters measured by MRI before RARP may be useful in the prediction of UI. In particular, MUL and LAM can predict postoperative UI by strict definition.